A 'degradable' poly(vinyl alcohol) iron oxide nanoparticle hydrogel. (August 2017) - Bannerman, A. Dawn; Li, Xinyi; Wan, Wankei
Graphical abstract: Abstract: Polymeric materials that contain magnetic nanoparticles are extremely useful in many applications including as multifunctional drug carriers, imaging contrast agents, or scaffold material. There is a need for biomaterials with appropriate chemical, mechanical, and magnetic properties that also have the ability to degrade or dissolve over time so they can be eliminated from the body following use. In this work, we explore the use of iron oxide nanoparticle (IONP) formation in poly(vinyl alcohol) (PVA) as a crosslinking method in conjunction with physical crosslinking achieved using low temperature thermal cycling (LTTC). PVA-IONP hydrogels were fabricated and characterized. IONPs contribute to the crosslinking of the PVA-IONP material, and their subsequent removal reduces crosslinking, and therefore stability, of the material, allowing dissolution to occur. Dissolution studies were performed on PVA-IONP hydrogels and dissolution was compared for films in solutions of varying pH, in the presence of iron chelating agents, and in simulated physiological and tumor conditions in cell culture media. Iron release, mass loss, and mechanical testing data was collected. This work demonstrates the ability of this biomaterial to 'degrade' over time, which may be very advantageous for applications such as drug delivery. This importance of this work extends to other areas such as the use of stimuli-responsive hydrogels. Statement of Significance: This manuscript explores the stability of an iron oxide nanoparticle (IONP)-containing, physically crosslinked poly(vinyl alcohol) (PVA) hydrogel. The PVA-IONP hydrogel's stability is imparted through crosslinks created through a low temperature thermal cycling process and through the IONPs. Subsequent IONP removal reduces crosslinks so material dissolution can occur, resulting in a 'degradable' and multifunctional biomaterial. PVA-IONP films were fabricated, characterized and evaluated in terms of dissolution in solutions of varying pH and in the presence of chelating agents. Iron release, mass loss, and mechanical testing data demonstrate the ability of the PVA-IONP biomaterial to 'degrade' over time. This degradability has not yet been demonstrated for crosslinked PVA hydrogels. These results are relevant to the development of degradable multifunctional drug carriers, image contrast agents, or magnetic scaffold materials.